Effects of slow and deep breathing on reducing obstetric intervention in women with pregnancy-induced hypertension: a feasibility study protocol - M. Felton; V. A. Hundley; S. Grigsby; A. K. McConnell (Taylor & Francis Group, 2021)
Objective: To evaluate whether a slow and deep breathing (SDB) intervention is acceptable to pregnant women. Methods: The trial aims to recruit 67 pregnant women who have developed pregnancy-induced hypertension (clinicaltrials.gov: NCT04059822). SDB will be undertaken daily for 10 min using a video aid and women will self-monitor blood pressure (BP) daily. At 36-weeks gestation women will complete an online questionnaire. Adherence, recruitment rates, and acceptance of the intervention will be evaluated. Conclusion: The findings from this trial will evaluate if women accept SDB as a treatment method. Initial analysis will evaluate if BP and/or obstetric interventions reduce following SDB intervention.